The overlap between burnout and depression through a different lens: A multi-method study - Baptista, Makilim Nunes; Hauck-Filho, Nelson; Cardoso, Hugo Ferrari [UNESP] (Elsevier, 2022)
Introduction: Depression and burnout are highly overlapping constructs, according to many correlational, factor, network, and mixture analysis studies. However, the latent correlation between the unique factors of burnout and depression might be confounded by a general factor of distress, and acquiescence (i.e., the tendency to agree more than disagree when responding to self-report items). In the current study, we performed an in-depth investigation on the latent structure of burnout and depression controlling for a general factor and acquiescence, and using a combination of random-intercept bifactor, network, and latent profile analysis. Method: Participants were 584 nurse professionals (79% nurse technicians and assistants, 21% nurses), with ages ranging from 20 to 65 years (M = 35.41; SD = 9.54), who responded to measures of depression symptoms, burnout, and work stress. Results: Results revealed a latent overlap between depression and burnout, even once acquiescence (r = .74), and a general factor was accounted for (r = .57). Burnout and depression indicators formed a coherent network of associated symptoms, with fatigue and lack of energy acting as bridge symptoms. The latent profile analysis yielded five classes that once again suggested a high dependence between burnout and depression. Discussion: We conclude that controlling for acquiescence and a general factor does not eliminate the high overlap between burnout and depression, that fatigue symptoms bear clinical importance as a trigger to more severe mental suffering in occupational settings, and that burnout involves a continuum of work stress.
Keywords: Affective disorders; Cluster analysis; Construct overlap; Distress; Job stress; Occupational health